Estimating Everyday Neuropsychological Functioning in Multiple Sclerosis: Reliability and Validity of the Greek Multiple Sclerosis Neuropsychological Questionnaire. (25th September 2018) - Konstantinopoulou, Eleni; Ioannidis, Panagiotis; Bakirtzis, Christos; Giantzi, Virginia; Afrantou, Theodora; Parissis, Dimitrios; Messinis, Lambros; Nasios, Grigorios; Grigoriadis, Nikolaos
Abstract : The Multiple Sclerosis Neuropsychological Questionnaire is a brief screening questionnaire for the assessment of everyday neuropsychological competence of patients with Multiple Sclerosis. The aim of the present study was to examine psychometric properties of the Greek version of the instrument. One hundred and three MS patients and 60 informants participated in the present study and completed the questionnaire. From the initial patient sample, 51 participants completed broadly used neuropsychological tests and measures estimating cognitive failures and depression. Moreover, after a six-month interval the MSNQ was administered to 58 patients from the initial sample in order to explore test-retest reliability. Cronbach's α was 0.92 and 0.93 for patient and informant forms, respectively. The patient form was correlated significantly with measures of cognitive failures and depression. Low correlations were found between the informant form and performance on cognitive tests. In regard to the patient form, significant correlation was observed between repeated administrations and, psychometrically, the three-factor structure was preferable than the one-factor structure. The present study confirms the already established pattern of correlations among the two MSNQ forms, neuropsychological test performance and depression measurements. Additional research is needed in order to define a cut-off score for the MSNQ-I providing further information about the diagnostic interpretability of the instrument.